Peran Pemuda dalam Membangun Tolerasi Umat Beragama: (Studi Kasus Muda-Mudi Dusun Matanari) - Hamidah Azzahra S Lubis; Ryan Taufika; Ummi Salamah Lubis (Kamaya: Jurnal Ilmu Agama, 2023)
The role of youth is very important in building a spirit of tolerance in society. This research aims to examine the role of youth in building a spirit of tolerance in society. The research was conducted in Matanari hamlet, Ujung Teran Village, Dairi. This research uses a qualitative case study type approach. The subjects in this research were community leaders (JM), representatives of youth leaders (BM and TSM). Data was collected using semi-structured interviews, observation and documentation, and enriched through literature review. The data was then analyzed using the Miles and Huberman model (1994). The results of this research conclude that Matanari young people play an active role in building religious tolerance in Matanari hamlet. Matanari youth have routine activities that contribute to building religious tolerance, such as merkebbas activities during village parties/events and Halal Bil Halal activities for Eid al-Fitr and New Year celebrations. This activity is carried out regularly and has been passed down from generation to generation. Every Eid al-Fitr and New Year event is held every year. In each event, religious figures from both Islam and Christianity were given the opportunity to give speeches. Apart from that, this is a form of tolerance education for teenagers (primary and junior high school age children) through involvement in these activities. The role of support from parents/community figures is very important in these activities. This research is still very limited in terms of time, depth of material, and coverage of the area and research respondents. Therefore, more in-depth study and research is needed in the future.